Peripheralization, Political Discontent, and Social and Solidarity Economy—Case Studies From Rural Hungary and Germany - Mihály, Melinda (Frontiers in Political Science, 2022)
The reintegration of Central and Eastern European (CEE) economies into globalized capitalism resulted in increasing regional polarization and the emergence of internal peripheries. The crisis of the globalized capitalist economy in 2008 resulted in the further peripheralization of rural areas, and the related crisis of representative democracies triggered rural resentment against the existing order. Inhabitants of peripheralized areas have a feeling of abandonment and political discontent. The rise of right-wing populism may be understood as a revolt of people living in precarious conditions in peripheralized areas both in Hungary and Germany. Left-wing populism, which builds on equality and social justice and is based on radical democracy, has not been able so far to reach the precaritized inhabitants of peripheralized rural areas. Solidarity economy, which is a contemporary social movement, refers to a comprehensive program aimed at transforming the entire economy, and may have the potential to address the political discontent of people living in peripheralized rural areas. In spite of the rising support for right-wing populism, social and solidarity economy (SSE) initiatives are being carried out in rural peripheries. These initiatives are based on the principles of participatory and economic democracy. Spaces provided by SSE initiatives can become forums for deliberation and co-management to develop economic democracy and become seeds of a solidarity economy movement in CEE. Therefore, based on a critical realist ethnographic approach, this paper aims to answer the question of how SSE initiatives may address the everyday material challenges and political discontent of people living in peripheralized villages by studying two SSE initiatives being carried out in two contrasting cases of peripheralization. Studying SSE initiatives in relation to 1) the locality they are embedded in, 2) “subaltern” groups within the locality, and 3) participatory, economic and 4) representative democracy helps to better understand in what ways SSE initiatives can mobilize political discontent to strengthen the solidarity economy movement in CEE.